Effective Management of Active Management in the Third Stage of Childbirth (Literature Review) - Woro Setia Ningtyas; Izzatul Ainiyah (Rifa'Institute, 2022)
Maternal mortality is still a global health issue even though it is decreasing every year. In Indonesia, based on the 2015 SUPAS, the maternal mortality rate reached 305 per 100000 live births, this figure is still very far from the SDGs target (Bappenas, 2017). Postpartum hemorrhage or better known as post-partum hemorrhage (HPP) is a cause of maternal death with an incidence of 1%-6% of all deliveries (Wormer et al., 2022). One of the efforts to prevent the occurrence of HPP is by implementing active management in the third stage of labor. This discussion aims to collect and analyze articles to identify the effectiveness of active management as a treatment for the third stage of labor. The results of this discussion show that the management of the third stage of labor with an active management approach reduces the amount of blood loss and shortens the duration of the third stage of labor compared to physiological management. However, these studies have low or even very low quality. Meanwhile, research on the active management measures of the third stage showed insignificant results regarding the main outcome in the form of the amount of bleeding. So that further research is needed regarding the effectiveness of the application of active management in the management of the third stage of labor and whether active management should be carried out in all low-risk and high-risk patients.